A voz dissonante de Lélia Gonzalez e o feminismo negro no Brasil - Ana Carolina dos Reis Fernandes (Les Cahiers ALHIM)
This article aims to present the contributions of Lélia González regarding the construction of black feminism in Brazil in the second half of the 20th century, both in the production of knowledge and in the militant practice, seeking to break with the paradigms of thought coming from a colonial background of power, still present in our society. According to her analysis, due to the history of our colonization, the black woman would face a triple process of discrimination, involving the categories of race and gender and the problems derived from class struggle. In this sense, the author defends a relevant and urgent question to be addressed by the women's movement: what is the place of the black woman in our society?